The impact of attitude markers on enhancing evaluation in the review article genre - Ali Sorayyaei Azar,; Azirah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Academic review writing is not merely about providing an overview but taking a stance and evaluating other scholars’ views in evaluation-loaded texts. In academic review genres, the authors describe, analyse, and evaluate the developments of a research. Perhaps the most noticeable way of such an evaluation in academic review genres is the use of attitudinal lexicon and its categories. The main aim of this research is (1) to investigate what type of attitude markers are frequently used to enhance evaluation in the review articles, and (2) to analyse their functions in the different analytical sections of the review articles. The data, drawn from a randomly selected corpus of thirty-two review articles, was analysed using Wordsmith tools (Scott, 2012) to investigate how evaluation was enhanced by the use of attitudinal lexicon. The results indicated that the attitude markers were more frequent in the Conclusion section than other analytical sections in the corpus. Four types of attitude markers were identified, however only two types (i.e. attitudinal adjectives and adverbs) were the most frequent markers. They appeared more frequently in Move2 and Move3 of the Conclusion sections. This study revealed how the authors professionally communicate with their readers to clarify their evaluation through attitude markers and express importance, limitations and gaps, compare and contrast, and praise and criticize the developments of a research in applied linguistics. The findings of this research can be drawn on in EAP courses for novice writers to facilitate their achievement in academic writing.